Combined sprint interval, plyometric, and strength training in adolescent soccer players: Effects on measures of speed, strength, power, change of direction, and anaerobic capacity - Ferley, D. D.; Scholten, S.; Vukovich, M. D. (The Journal of Strength and Conditioning Research, 2020)
During winter, many soccer players train indoors to improve the aerobic and anaerobic demands of their sport. Sprint interval training (SIT) performed on a treadmill using level and graded conditions represents a viable alternative to traditional endurance conditioning. To date, little research exists contrasting the effects of these conditions. Therefore, the purpose of this investigation included examining the effects of 2 approaches combining SIT, plyometrics, and strength training on performance measures in soccer players aged 13-18 years over 8 weeks. Forty-six subjects were divided into 3 groups. Group 1 performed SIT using predominantly inclined treadmill conditions combined with resistance and plyometric training (INC, n = 17). Group 2 performed SIT using level treadmill grades and completed the same resistance and plyometric training (LEV, n = 14). Group 3 was a control group representing various sports who continued their normal training (CON, n = 15). Pre- and posttests assessed speed, strength, change of direction, and anaerobic capacity, including sprint speed (9.1 and 18.3 m sprint), unilateral triple hop for distance (3HOP_L and 3HOP_R), pro agility change of direction (PA); treadmill running to exhaustion on a 20% grade (CFMod), and hip flexor maximum strength (HF_1RM). After training, INC and LEV improved more in all measures compared with CON. Furthermore, INC improved significantly more compared with LEV in 9.1- and 18.3-m sprint, 3HOP_L and 3HOP_R, PA, CFMod, and HF_1RM (p < 0.05). We conclude that strength and plyometric training combined with incline-based SIT is more effective than a similar training approach using level-grade SIT.